A decade of Nigeria politics, economy and society, 2004-2016 - Bergstresser, Heinrich 1949- (A decade of ... series, 2017)
This chronology for 2004 to 2015 compiles the chapters on Nigeria previously published in the 'Africa Yearbook. Politics, Economy and Society South of the Sahara'. This decade, however, covers the most crucial events such as stabilising the democratic process, a short-lived economic boom, the rise of Boko Haram and its Islamist insurgency, the amnesty and the renewed violence in the Niger Delta, the rise of unprecedented crime in the Middle Belt and the election defeat of a sitting president. In a sense, all these events were shaping the country?s political and socioeconomic system and are having a long-lasting impact